Good hearts - Price, Reynolds 1933-2011 (Atheneum, 1988)
The author continues the story of Rosacoke (Rosa) Mustian and Wesley Beavers, now married for twenty-eight years, as Wesley strays to Nashville with a younger woman.
Keywords: Married people -- Fiction; Mustian, Rosacoke (Fictitious character) -- Fiction; Love stories